Pentingnya Kajian Sosiologi Pendidikan Islam bagi Calon Pendidik - Siti Wulandari; Taqiyyatunnisa’ Maulidy Azababilah; Wardatuz Zahro’ul Mukaromah; Jakaria Umro (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2026)
Islamic Educational Sociology is a discipline that explores how Islamic education interacts with and is influenced by social life in society. For future educators, mastering this field is crucial, as it offers a deeper understanding of students’ social backgrounds, behaviors, and the surrounding environmental factors that shape the learning process. This article seeks to highlight the significance of Islamic Educational Sociology in helping prospective educators להתמודד the complexities and evolving dynamics of modern society. The research uses a literature review approach by examining various relevant sources on sociology and Islamic education. The results show that this field equips future educators with the ability to appreciate social diversity, build effective relationships with students, and incorporate Islamic values into teaching practices. In addition, awareness of social realities allows educators to design learning experiences that are more relevant, inclusive, and responsive to learners’ needs. Consequently, Islamic Educational Sociology becomes a vital foundation for prospective educators in developing quality education that is human-centered, adaptable, and rooted in Islamic principles.